Andersen’s Health Behavioral Model of Health in Reproductive Maternal Health Services: A Narrative Review from 2012-2024 - Jannatul Ferdous Tora; Md. Reazul Islam (CenRaPS Journal of Social Sciences, 2026)
This study explores and examined the application of health behavioral model by Ronald M. Andersen. The model breaks things into three primary variables, such as predisposing factors, enabling factors, and need factors. Such a review would help us understand how widely the model is being used, what methods are being used by researchers and where more research is needed. This current study is a narrative review and aims to evaluate the use and execution of the behavioral model of health services use developed by Ronald M. Andersen that was published from 2012 to 2024. This study is the content-based secondary literature review. In July 2025, we conducted a secondary literature search on PubMed, Google Scholar and ScienceDirect. Eligible studies that applied Andersen's Behavioral Model in reproductive or maternal healthcare were included. Data were extracted and synthesized narratively according to the model's three core domains: predisposing, enabling, and need factors. Andersen's behavioral model of health services utilization was applied in the studies as a guide to help understand why people seek or do not pursue medical attention. In 15 out of 15 studies, age was the reason why people used or did not use healthcare. How many people had the main thing that helped them get to healthcare in 13 out of 15 studies? Whether people thought they needed healthcare was the main reason why they used healthcare in 14 out of 15 studies. The studies mostly concentrated on women who are of reproductive age. The studies also showed that women are more likely to use healthcare than men when it comes to health. This model can help policymakers and people who design programs identify things that might stop people from using healthcare and things that might help them use it. As a whole, the results show that getting reproductive and maternal healthcare is not influenced by one thing but by many factors, like social, cultural, economic and structural issues.